Results of the Study for the Antihypertensive Effect in the Panzeria Alaschanica Kupr Plant - Ha La Tu, Hu Bi Si; Tumurbaatar, Khaliunaa; Chimedtseren, Chimedragchaa; Bukhbayar, Tsogt; Damba, Tsend-Ayush (Central Asian Journal of Medical Sciences, 2022)
Objectives: To study the effect of the plant Panzeria alaschanica Kupr on lowering blood pressure. Methods: The experiment was performed using Sharon Leng Hong Ong (2009) using a male rat weighing 150 - 250 grams. On days 5, 8, 13, and 15 of the experiment, ECG, heart rate, and arterial pressure were measured in the rat’s tail with a Neurobotic systole 1.2 instruments. At the end of the experiment, the content of renin, angiotensin II and aldosterone were determined by enzyme-linked immunosorbent assay. Results: According to the results of the study, the experimental group of plant Panzeria alaschanica Kupr ingested a dose of 160 mg/kg of renin 36.8 % compared with the control group that caused the pathological model, the amount of aldosterone in animals plant Panzeria alaschanica Kupr who ingested a dose of 32 mg/kg were 43.5 % of the ingested animals compared with the pathogenic group, the amount of angiotensin II in the plant Panzeria alaschanica Kupr was 64 mg/kg animals that ingested in, was reduced by a statistically significant difference (p < 0.05) of 34.3 % compared with the control group generated by the pathological model. Conclusion: Panzeria alaschanica Kupr has a 36.8 % reduced blood pressure by affecting the renin, angiotensin, and aldosterone systems.